Transformasi Bisnis di Era Digital: Analisis Sistematis Terhadap E-Bisnis di Indonesia Pada Konteks UMKM - Septiadi, Bayu; Agus, Isnandar (Puslitbang Akademi Relawan TIK Indonesia, 2024)
Business transformation in the digital era and systematic analysis of e-business in Indonesia, especially in the context of UMKM (Micro, Small and Medium Enterprises). The growth of e-business in Indonesia is related to technological advances and changes in consumer behavior. This article aims to provide a comprehensive understanding of developments, challenges and potential solutions to support UMKM business transformation in the digital era. Some of the topics studied include the role of e-business in the transformation of UMKM in Indonesia, challenges in adopting e-business technology, effective strategies for encouraging e-business adoption among UMKM, and the impact of business transformation through e-business on local economic growth. The research method uses a systematic literature review (SLR) approach to investigate and analyze relevant literature. The findings from this research show that e-business has an important role in the development of UMKM in Indonesia, but UMKM still face challenges in adopting digital technology. Therefore, an effective strategy is needed to encourage the adoption of e-business among UMKM and the impact of business transformation through e-business can make a positive contribution to local economic growth. It is hoped that this research can support the development and sustainability of UMKM in Indonesia in this digital era.